A transcriptional journey from sucrose to endosperm oil bodies in triple transgene oily wheat grain. (July 2021) - Larkin, P.J.; Zhou, X.R.; Liu, Q.; Reynolds, K.; Vanhercke, T.; Ral, J.P.; Li, Z.; Wu, X.B.; Yu, R.; Luo, J.X.; Newberry, M.; Howitt, C.H.
Abstract: Transgenic wheat expressing Wrinkled1 (Wri1), diacylglycerol acyltransferase 1 (DGAT1), and Oleosin genes with endosperm active promoters, in the companion paper were found to accumulate 5–10 times the quantity of triacylglyceride (TAG) in the endosperm compared to the control. In this study we track the pleiotropic effects on transcription at four grain development time points, of genes whose products are involved in the various pathways from sugar import to oil body formation, as well as other major metabolic pathways in the developing grain. The transcriptional impacts were substantial with early increases in genes for sucrose transport, hexose phosphate formation, cytoplasmic glycolysis, and ADP-glucose transport to the plastid. Corresponding to the late expression of the Wrinkled1 transgene, there was a late up-regulation of the entire suite of genes in the plastidial fatty acid synthesis pathway. Transport of fatty acid precursors to the ER was likely facilitated by early up-regulation of FAX1 (Fatty acid export) and LACS8 (long-chain acyl-CoA synthetase) genes. With the exception of the transgenic DGAT1, there were relatively few and moderate changes to transcription of other genes involved in TAG assembly in the ER, although the direct use of the acyl-PC pool appears to be down-regulated. A large up-regulation was observed at the three earliest time points of many genes associated with the formation of lipid droplets, including endogenous oleosins, caleosins, stereoleosins, seipins, and a variety of other lipid body associated proteins. Also unanticipated was the early down-regulation of a number of genes whose products are involved in lipid body turnover and peroxisomal β-oxidation of released fatty acids. Despite the substantial increase in TAG accumulation, the transgenic grains were not reduced in starch or protein and the transcriptional analysis demonstrated an early up-regulation of the entire suite of starch synthesis genes and protein storage genes. Graphical abstract: Image 1 Highlights: Transgenic wheat with high endosperm oil has many transcriptional effects. Early up-regulation of sucrose import and ADP-glucose transport to the plastid. Late up-regulation of plastidial fatty acid synthesis corresponding to Wrinkled1. Early up-regulation of fatty acid transport to ER but little change to TAG assembly. Up-regulation of lipid body associated proteins and down-regulation of lipid turnover.